Pengaruh Enterprise Risk Management, Tata Kelola, Sistem Informasi Risiko, dan Leverage terhadap Kinerja Keuangan Bank BUMN - Mochammad Nugraha Reza Pradana; Suherman Suherman; Angelin Angelin; Ferdy Jason; Viona Anggreany; Michelle Michelle (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The banking business is confronted with more intricate risks as a result of digital revolution, more regulation, and shifting financial market conditions. It is the purpose of this research to examine how state-owned banks in Indonesia fare financially in relation to ERM, corporate governance, risk management information systems, and leverage. This study employs a quantitative explanatory methodology based on secondary data culled from the 2018–2025 annual reports, financial statements, and corporate governance reports of Bank Mandiri, BRI, BNI, and BTN. Descriptive statistics, assessments of classical assumptions, and multiple linear regression were employed to examine the records. The results demonstrate that Enterprise Risk Management influences financial performance in a favorable and statistically significant way, suggesting that integrated risk management contributes to increased profitability. The fact that leverage has a positive effect indicates that, with good management, debt can boost financial performance. When looking at corporate governance, the size of the board of commissioners is not a strong indicator of financial performance. On the other hand, there is a notable impact from the risk management information system, however it is important to approach its interpretation with care because of multicollinearity and the lack of data variation. According to these results, in order for state-owned banks to keep their financial performance in the long run, they should optimize their leverage, increase the quality of their risk information systems, and enhance integrated risk management.